The Effect of Surface Roughness of a Body in the High Reynolds-Number Flow - Tsutomu adachi (International Journal of Rotating Machinery)
In this paper, first, the principle, structures, operations, and performances of the cryogenic wind tunnel are described. By changing the pressure, temperature and velocity of gas a high Reynolds-number flow (5×104<Re<107) can be obtained. From the research results, a high Reynolds-number flow with comparatively low power, LN consumptions was attained. It was with Mach-number independent of each other, o show some examples of high Reynolds-number flow, the effects of surface roughness and grooves on the surface of a cylinder on the flow are measured using models with various values of roughness and size. A model test of an airship was also conducted. With the high Reynolds-number flow, the thickness of the boundary layer becomes thinner. Then the surface conditions of a body have great effect on the flow phenomena and on the drag of the body. Some attempts to reduce the drag of the body were shown.